Flexural Performance of a Hybrid Bridge Deck with Pultruded Fibre Reinforced Polymer Composite Sandwich Panels - Lei Wu; Yujun Qi; Weiqing Liu (The Baltic Journal of Road and Bridge Engineering)
Hybrid bridge decks with the pultruded fibre reinforced polymer have advantageous properties but easily crack because of their unsatisfactory transverse strength and shear strength. This study proposed a type of bridge deck composed of innovative pultruded fibre reinforced polymer composite sandwich panels. Using four-point bending tests, concentric wheelloading tests and eccentric wheel-loading tests combined with first-order shear deformation theory, this study investigated the failure mode, flexural capacity, deformation and ductility of hybrid bridge decks under different working conditions. Under four-point bending and concentric wheel loading, the primary failure modes for this hybrid bridge deck were shear failures along the fibre direction and buckling failure of the upper panel. Under eccentric wheel loading, the primary failure mode was a torsional failure due to the eccentric load. The bearing capacities of the hybrid bridge deck under the three working conditions were 3.8, 3.5 and 3.2 times the service load of a Class I vehicle load, respectively. Besides, the hybrid bridge deck remained in the linear elastic stress state at 2.6 times the service load, indicating that this hybrid bridge deck withstands relatively large vehicle overload without visible damage. The ductility values of this hybrid bridge deck under the three working conditions were 1.79, 2.09 and 2.00, respectively, which are higher than the values for an ordinary pultruded bridge deck. Therefore, the proposed design has the relatively good energy-dissipating capacity, which improves the emergency capacity of the bridge deck.